Point‐of‐care viral load monitoring: outcomes from a decentralized HIV programme in Malawi. Issue 8 (23rd August 2019) - Nicholas, Sarala; Poulet, Elisabeth; Wolters, Liselotte; Wapling, Johanna; Rakesh, Ankur; Amoros, Isabel; Szumilin, Elisabeth; Gueguen, Monique; Schramm, Birgit
Abstract: Introduction: Routinely monitoring the HIV viral load (VL) of people living with HIV (PLHIV) on anti‐retroviral therapy (ART) facilitates intensive adherence counselling and faster ART regimen switch when treatment failure is indicated. Yet standard VL‐testing in centralized laboratories can be time‐intensive and logistically difficult in low‐resource settings. This paper evaluates the outcomes of the first four years of routine VL‐monitoring using Point‐of‐Care technology, implemented by Médecins Sans Frontières (MSF) in rural clinics in Malawi. Methods: We conducted a retrospective cohort analysis of patients eligible for routine VL‐ testing between 2013 and 2017 in four decentralized ART‐clinics and the district hospital in Chiradzulu, Malawi. We assessed VL‐testing coverage and the treatment failure cascade (from suspected failure (first VL>1000 copies/mL) to VL suppression post regimen switch). We used descriptive statistics and multivariate logistic regression to assess factors associated with suspected failure. Results and Discussion: Among 21, 400 eligible patients, VL‐testing coverage was 85% and VL suppression was found in 89% of those tested. In the decentralized clinics, 88% of test results were reviewed on the same day as blood collection, whereas in the district hospital the median turnaround‐time for results was 85 days. Among first‐line ART patients with suspected failure (N = 1544), 30% suppressed (VL<1000 copies/mL), 35% were treatment failures (confirmed by subsequent VL‐testing) and 35% had incomplete VL follow‐up. Among treatment failures, 80% (N = 540) were switched to a second‐line regimen, with a higher switching rate in the decentralized clinics than in the district hospital (86% vs. 67%, p  < 0.01) and a shorter median time‐to‐switch (6.8 months vs. 9.7 months, p  < 0.01). Similarly, the post‐switch VL‐testing rate was markedly higher in the decentralized clinics (61% vs. 26%, p  < 0.01). Overall, 79% of patients with a post‐switch VL‐test were suppressed. Conclusions: Viral load testing at the point‐of‐care in Chiradzulu, Malawi achieved high coverage and good drug regimen switch rates among those identified as treatment failures. In decentralized clinics, same‐day test results and shorter time‐to‐switch illustrated the game‐changing potential of POC‐based VL‐testing. Nevertheless, gaps were identified along all steps of the failure cascade. Regular staff training, continuous monitoring and creating demand are essential to the success of routine VL‐testing.